PENGARUH KETERAMPILAN MANAJERIAL DAN KEPEMIMPINAN KEPALA SEKOLAH SEKOLAH TERHADAP KEPUASAN KERJA GURU SMP SWASTA SE-KOTA PEKANBARU - Henderina, Henderina; Ernamaiyanti, Ernamaiyanti (Perspektif, 2018)
The principal is required to have inner skills. That ability will determine whether or not education succeeds on going learning at school. In addition, the principal should also pay attention to the work satisfaction of teachers in the work environment. The purpose of this research is to know 1) to know the influence of managerial skill to job satisfaction of Private Junior High School teachers in Pekanbaru City, 2) to know the influence of leadership capability of headmaster to job satisfaction of junior high school teacher of Pekanbaru City, 3) to know the effect of managerial training and leadership of the principal together towards the job satisfaction of Private Junior High School teachers in Pekanbaru City. This research is a quantitative research with the determination of respondents apply Solvin formula as many as 93 respondents with subject of Private Junior High School as Pekanbaru City. Data type is primary data and secondary data. Data processing methods with editing, coding, scoring process. Data were analyzed by multiple linear regression. The findings of this study include 1) positive managerial skills to teacher work satisfaction of 0.232 or equivalent to 23.2%; 2) leadership ability of headmaster positively influence to job satisfaction of teacher equal to 0,342 or equal to 34,2%; 3) managerial and leadership skills of principals together have a significant positive effect on the dependent variable of job satisfaction of teachers in private Junior High School Pekanbaru.